Improving mediated electron transport in anodic bioelectrocatalysis1. Issue 61 (7th August 2015) - Tao, Le; Wang, Haibo; Xie, Mingshi; Thia, Larissa; Chen, Wei Ning; Wang, Xin
<x xml:space="preserve">Abstract</x> A microbial fuel cell loaded with bio-cocatalyst beads immobilized with recombinant riboflavin-secreting Escherichia coli shows significantly enhanced performance.